2021
DOI: 10.3390/biomedicines9091212
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pulse Wave Transit Time with Pulmonary Artery Pressure in a Porcine Model of Pulmonary Hypertension

Abstract: For the non-invasive assessment of pulmonary artery pressure (PAP), surrogates like pulse wave transit time (PWTT) have been proposed. The aim of this study was to invasively validate for which kind of PAP (systolic, mean, or diastolic) PWTT is the best surrogate parameter. To assess both PWTT and PAP in six healthy pigs, two pulmonary artery Mikro-Tip™ catheters were inserted into the pulmonary vasculature at a fixed distance: one in the pulmonary artery trunk, and a second one in a distal segment of the pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…investigated the relationship between the pPTT and the estimated pulmonary artery pressure in the porcine model of pulmonary arterial hypertension and found a negative correlation between pPTT and calculated sPAP. [ 21 ] The outcomes of our study were comparable with their reports and demonstrated the strong association between pPTT and impaired pulmonary functions. According to our study, estimated TAPSE, RV FAC, and pPTT measurements were significantly lower among COVID-19 survivors compared to healthy control subjects ( P < 0.05, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…investigated the relationship between the pPTT and the estimated pulmonary artery pressure in the porcine model of pulmonary arterial hypertension and found a negative correlation between pPTT and calculated sPAP. [ 21 ] The outcomes of our study were comparable with their reports and demonstrated the strong association between pPTT and impaired pulmonary functions. According to our study, estimated TAPSE, RV FAC, and pPTT measurements were significantly lower among COVID-19 survivors compared to healthy control subjects ( P < 0.05, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…According to these studies, this novel index not only identi ed the severity of pulmonary brosis but act as a potential index of pulmonary dysfunction [9]. In another study, Mueller-Graf et al investigated the relationship between the pPTT and the estimated pulmonary artery pressure in the porcine model of pulmonary arterial hypertension and found a negative correlation between pPTT and calculated sPAP [21]. Outcomes of our study were comparable with their reports and demonstrated the strong association between pPTT and impaired pulmonary functions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the peak late systolic (S2), peak diastolic (D) and atrial reversal (A) velocities can be identified from the pulmonary vein spectrum in normal adults. Then, pPTT, defined as the time interval between the R‐wave in the electrocardiogram and the corresponding peak late systolic pulmonary vein flow velocity (R‐PVs2 interval) was measured (Figure 1) (Dogan et al, 2018; Efe et al, 2017; Mueller‐Graf et al, 2021; Wibmer et al, 2015). The pPTT values were measured from three consecutive beats at least and averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary pulse wave transit time (pPTT), defined as the time it takes for the systolic pressure pulse wave to travel from the pulmonary valve to the pulmonary veins, has been recognized as a useful surrogate marker of pulmonary hemodynamic and vascular alterations in pulmonary hypertension (Mueller‐Graf et al, 2021; Prins et al, 2016; Wibmer et al, 2015), pulmonary fibrosis (Wibmer et al, 2015), systemic lupus erythematosus (Efe et al, 2017), systemic sclerosis (Dogan et al, 2018) and other related diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation